Spectroscopy and serial diffusion MR findings in hGH-Creutzfeldt-Jakob disease. Issue 7 (16th June 2004) - Oppenheim, C; Zuber, M; Galanaud, D; Detilleux, M; Bolgert, F; Mas, J L; Chiras, J; Meder, J F
Abstract : This report describes the magnetic resonance imaging (MRI) findings in two patients fulfilling the diagnostic criteria for human growth hormone Creutzfeldt-Jakob disease, who initially had pronounced bilateral DWI/FLAIR (diffusion weighted imaging/fluid attenuated inversion recovery) hyperintensities in the basal ganglia, with decreased apparent diffusion coefficient (ADC) values ( range, 58–82% of normal) . MRI spectroscopy, obtained in one case, showed decreased N -acetyl aspartate/creatine (NAA/Cr) ratio in the atrophic vermis (0.79; normal: mean, 1.20; SD, 0.13), despite the lack of DWI/FLAIR signal changes, whereas NAA/Cr was normal in the putamina (1.6; normal: mean, 1.56; SD, 0.17), despite striking DWI signal changes and decreased ADC values (60% of normal). Serial DWI, obtained in the other case, showed a progressive disappearance of DWI hypersignal of the basal ganglia replaced by pronounced atrophy. Data from these two patients suggest that restricted diffusion associated with a normal NAA value might indicate spongiform changes of still viable cells, and that any subsequent regression of the DWI signal changes, atrophy, or decreased NAA values could be related to progressive neuronal death.